Penguatan Kapasitas Kader Dan Optimalisasi Pusat Edukasi Gizi Untuk Meningkatkan Kesehatan Balita - Mudarifa Wulandari Syamsul Arifin; Putri Amelda; Amelia Nur Sayida; Putri Kusuma Cahayani; Annif Munjidah (LPPI UMN AL WASHLIYAH, 2025)
The main issue raised is the high rate of nutritional disorders among toddlers in Indonesia, such as stunting, wasting, and underweight, which indicates that efforts to improve children's nutritional status have not been optimal. Although the toddler period is the 'golden period' for growth and development, inadequate nutrition can lead to nutritional disorders that affect organ development, nerve function, and the immune system, as well as decrease intelligence. In addition, there are still limitations in the capacity of health cadres in detecting nutritional status and providing counseling, including exclusive breastfeeding counseling and Infant and Young Child Feeding (IYCF). Community access to effective nutrition education centers is also still limited. Keywords: Toddler nutrition, Stunting, Health cadres, Nutrition education centers, Exclusive breastfeeding, IYCF, Nutrition counseling